Pengembangan Media Big Book Berbasis Cerita Rakyat Sumatera Utara dalam Meningkatkan Kemampuan Bercerita Siswa Kelas II SDS Muhammadiyah 36 Medan - Risma Handayani; Tri Indah Kusumawati; Auffah Yumni (INDO PUBLISHING, 2025)
Storytelling is an important communication skill to develop, especially for elementary school students. Because it not only plays an important role in academic matters, but is also useful in their daily lives. However, many elementary school students still lack self-confidence and have limited access to interesting learning media, resulting in students encountering obstacles when telling stories in front of the class. This study aims to determine whether the developed big book media is feasible, practical, and effective for use in learning to improve students' storytelling skills. This research is included in the category of research and development or Research and Development (R&D), with the ADDIE model, which consists of: Analysis, Design, Development, Implementation, and Evaluation. The results showed that the big book obtained a percentage of 83.6% (material experts), 100% (media experts), 80% (teacher responses), and 95% (student responses). The effectiveness of the big book media achieved an N-Gain score of 14.87 with an average N-Gain score of 0.51275862 and an N-Gain percentage of 51%. Based on the N-Gain criteria, the big book media can be categorized as quite effective so that the big book learning media can be used to improve the storytelling skills of second-grade students at SDS Muhammadiyah 36 Medan.